Poly(trimethylene carbonate-co-e-caprolactone) promotes axonal growth - Rocha, DN (2014)
Mammalian central nervous system (CNS) neurons do not regenerate after injury due to the inhibitory environment formed by the glial scar, largely constituted by myelin debris. The use of biomaterials to bridge the lesion area and the creation of an environment favoring axonal regeneration is an appealing approach, currently under investigation. This work aimed at assessing the suitability of three candidate polymers - poly(e-caprolactone), poly(trimethylene carbonate-co-e-caprolactone) (P(TMC-CL)) (11:89 mol%) and poly(trimethylene carbonate) - with the final goal of using these materials in the development of conduits to promote spinal cord regeneration. Poly(L-lysine) (PLL) coated polymeric films were tested for neuronal cell adhesion and neurite outgrowth. At similar PLL film area coverage conditions, neuronal polarization and axonal elongation was significantly higher on P(TMC-CL) films. Furthermore, cortical neurons cultured on P(TMC-CL) were able to extend neurites even when seeded onto myelin. This effect was found to be mediated by the glycogen synthase kinase 3ß (GSK3ß) signaling pathway with impact on the collapsin response mediator protein 4 (CRMP4), suggesting that besides surface topography, nanomechanical properties were implicated in this process. The obtained results indicate P(TMC-CL) as a promising material for CNS regenerativ e applications as it promotes axonal growth, overcoming myelin inhibition.